2013
DOI: 10.1007/s11356-013-1591-3
|View full text |Cite
|
Sign up to set email alerts
|

PCB 77 dechlorination products modulate pro-inflammatory events in vascular endothelial cells

Abstract: Persistent organic pollutants such as polychlorinated biphenyls (PCBs) are associated with detrimental health outcomes including cardiovascular diseases. Remediation of these compounds is a critical component of environmental policy. Although remediation efforts aim to completely remove toxicants, little is known about the effects of potential remediation byproducts. We previously published that Fe/Pd nanoparticles effectively dechlorinate PCB 77 to biphenyl, thus eliminating PCB-induced endothelial dysfunctio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 32 publications
1
17
0
Order By: Relevance
“…We have demonstrated previously that coplanar PCBs can cause endothelial dysfunction as evidenced by an upregulation of inflammatory mediators including the cytokine IL-6 and chemokine MCP-1 (Eske et al 2013; Han et al 2012; Majkova et al 2009). In fact, PCB 77-treated animals that were exposed to exercise had levels of inflammation that were not different from control sedentary animals.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We have demonstrated previously that coplanar PCBs can cause endothelial dysfunction as evidenced by an upregulation of inflammatory mediators including the cytokine IL-6 and chemokine MCP-1 (Eske et al 2013; Han et al 2012; Majkova et al 2009). In fact, PCB 77-treated animals that were exposed to exercise had levels of inflammation that were not different from control sedentary animals.…”
Section: Discussionmentioning
confidence: 99%
“…Because the endothelium is in immediate contact with blood, endothelial cells are particularly vulnerable to environmental contaminants present in the circulation and which can induce inflammation and endothelial dysfunction (Eske et al, 2013; Hennig et al, 2002). The majority of pro-inflammatory effects from coplanar PCBs are mediated through the aryl hydrocarbon receptor (AhR) (reviewed in (Petriello, Newsome, & Hennig, 2013)).…”
Section: Introductionmentioning
confidence: 99%
“…Dysfunction of the endothelium is regarded as an important factor in the pathology of atherosclerosis [7]. There is accumulating evidence that persistent organic pollutants such as PCBs can accelerate an inflammatory response in vascular tissues [1113, 22, 23, 41]. In the current studies, we demonstrated that EGCG significantly attenuated PCB 126-mediated induction of proatherogenic cytokines and adhesion molecules such as IL-6, CRP, ICAM-1, VCAM-1, and IL-1α/β in human endothelial cells.…”
Section: Discussionmentioning
confidence: 99%
“…Epidemiological studies provide substantial evidence that the pathology of CVD is associated with exposure to environmental pollutants, such as polychlorinated biphenyls (PCBs) [810]. Importantly, PCB exposure is believed to cause vascular inflammation through expression of several inflammatory markers, cytokines and adhesion molecules [1113]. Thus, these inflammatory markers may become potential therapeutic targets for nutritional intervention against CVD, which is triggered or enhanced by exposure to environmental pollutants.…”
Section: Introductionmentioning
confidence: 99%
“…There is sufficient evidence that POPs contribute to inflammation by activating oxidative stress-sensitive transcription factors such as nuclear factor kappa-light-chain-enhancer of activated B cells (NFκB) (Hennig et al, 2002). For example, our studies suggest that PCBs, and in particular coplanar PCBs, can increase cellular oxidative stress and induce inflammatory parameters such as inflammatory cytokines, chemokines, and adhesion molecules in the vascular endothelium, which are metabolic events that foster an inflammatory response and atherosclerosis (Eske et al, 2013; Hennig et al, 2002; Lim et al, 2007; Majkova et al, 2009). Through these pro-inflammatory mechanisms, PCBs and related environmental toxicants have been correlated with increased risk of multiple human chronic disease phenotypes including diabetes and heart disease (Carpenter, 2011; Goncharov et al, 2008; Silverstone et al, 2012; Uemura, 2012).…”
Section: Introductionmentioning
confidence: 95%